Flood hazard assessment of a flood-prone intensively urbanized area : a case study from Samsun Province, Turkey - Beden, Neslihan (Array, 2020)
Flooding is one of the most catastrophic events among the wide spectrum of natural disasters that impact human communities. The identification of floodprone areas and the probability of occurrence, or estimated return period, of flood events are fundamental to proper planning for flood management and minimization of the social and economic costs of flood damage. In this study, 1D/2D coupled flood models of the Mert River, which flows into the Black Sea at Samsun in north-central Turkey, were developed. Based on the flood modeling results, flood extent, flood depth and flood hazard maps for the river were produced and they showed that the study area is particularly flood prone, as evidenced by catastrophic flooding in 2012. Specifically, the estimated 100, 500 and 1000-year peak discharges would affect 184 ha, 262 ha and 304 ha, respectively, of the 1,200 ha study area. Hazard ratings for the areas expected to be affected are shown in the flood hazard maps generated. The results of this research can be used by local government agencies in Samsun for the development of policies, strategies and actions that would help minimize the social and economic impacts of flooding, especially adjacent to the downstream sections where there is intensive development on the flood plain.